Water Landscapes and History - Freitas, Isabel Vaz de (2017)
Heritage is composed by cultural assets, tangible and intangible, natural and environmental, that are the builders of Human History which must be preserved and protected for future generations. Protecting heritage is preserving the cultural memory of a community, the identity of a place, of a landscape. Protecting the asset for the visitor means to know it, communicate and interpret this heritage with the accuracy it deserves. In this work we intend to bring water’s importance to a wider audience, as part of the landscape, intending to join its history to raise awareness for the value of an essential good to men and to the territories.